E-235 Automated quantification of arcuate, superior longitudinal, and inferior longitudinal fasciculi using diffusion tensor tractography correlates with speech function in post-thrombectomy stroke patients. (23rd July 2022) - Abraham, B; Cunningham, C; Jaquish, R; Tobin, M; Limaye, K; Bohnstedt, B
Abstract : Background: Acute ischemic stroke (AIS) with a large vessel occlusion (LVO) has the potential to have significant neurological deficits. Mechanical thrombectomy has been shown to improve outcomes of AIS with LVO. Unfortunately, not all patients improve following embolectomy. Here, we use automated software to analyze diffusion tensor imaging (DTI) of the superior longitudinal, arcuate, and inferior longitudinal fasciculi to help understand why some patients' outcomes in speech are not as optimal. Methods: This is a retrospective study from June 2020 to June 2021 of AIS patients who underwent MT of the middle cerebral artery (MCA). Diffusion tensor images were acquired within 96 hours after MT. Proprietary software provided by Synaptive Medical© was utilized for the automated quantification of tractography to obtain tract counts of the arcuate, superior longitudinal, and inferior longitudinal fasciculi. We correlated these tract counts with Thrombolysis in Cerebral Infarction (TICI) scores, Western Aphasia Battery (WAB) test scores during the in-patient period, and modified Rankin scores (mRS) at discharge utilizing Spearman correlation analysis. Results: Out of the 20 patients studied, there were 10 left-MCA (50%) and 10 right-MCA (50%) LVO causing AIS. For left-sided stroke patients, the TICI scores (R=+0.643), WAB scores (spontaneous speech R=+0.642, repetition R=+0.630, object naming R=+0.681) and mRS scores at discharge (R=-0.693) correlated with arcuate and superior longitudinal fasciculi tract counts (all p<0.05). The inferior longitudinal fasciculus tract count also correlated with other WAB scores (functional content R=+0.658, sequential commands R=+0.665) (all p<0.05). Except for discharge mRS correlating with the arcuate and superior longitudinal fasciculi (R=-0.826, p=0.003), the remaining clinical measures were not correlated with right-sided stroke patients' arcuate, superior longitudinal, and inferior longitudinal fasciculi. Conclusion: For left-sided MCA occlusions, TICI scores were well correlated with increased arcuate and superior longitudinal fasciculi tract counts after MT. After recanalization of the left MCA, increased number of arcuate, superior longitudinal, and inferior longitudinal fasciculi tracts is associated with improved speech function measured by the WAB test. These two findings were not apparent in right-sided MCA occlusions, perhaps due to the minimal role of the right cerebral hemisphere in speech. Tract count analysis of the arcuate, superior longitudinal, and inferior longitudinal fasciculi for either right- or left-MCA occlusions correlated with discharge mRS, indicating that a higher number of tracts measured within 4 days of MT could act as a proxy for patient's overall independence status by discharge. While larger, prospective studies are needed to confirm these findings, automated tractography could yield novel avenues into patient screening during post-operative recovery of speech function. Disclosures: B. Abraham: None. C. Cunningham: None. R. Jaquish: None. M. Tobin: None. K. Limaye: None. B. Bohnstedt: 6; C; proctor/consultant.